How do People Say about Language, Culture, and Ideology? - Zamruddin, Mardliya Pratiwi (Journal of ELT, Linguistics, and Literature, 2017)
This article talks about definitions on language, culture, and ideology from several point of views and experts and also how the three are linked and connected and created relationship that the question of ˜Which comes first? or ˜Which one is more important? can only be answered by putting language, culture, and ideology together. This article also provides understanding on intercultural within the heterogeneous society as well as whether or not culture can be improved.